Territory and Digitalization. The Action of iFood in Campos dos Goytacazes Municipality,Rio de Janeiro State, Brazil - ´Souza, Nágila da Silva Ferreira; Silvana Cristina da Silva (Geografares, 2024)
Digital platforms make use of technologies and neoliberal rationality to expand their actions. This is about the exacerbation of the technical-scientific-informational environment. The question is, how do digital platforms reshape the urban fabric of cities? The goal here is to show how the expansion of the iFood app has taken place, with an analytical focus on the geographical situation of the municipality of Campos dos Goytacazes, Rio de Janeiro State, Brazil (2020-2022). The methodology used was a bibliographic survey; data collection on its website and app and information platforms associated with it; analysis of the company’s Instagram profile; interviews with couriers and registered establishments; systematization and analysis of data. In Campos dos Goytacazes, iFood reinforces the inequalities between the city center and the periphery. Additionally, the platform intensifies information flows to expand its activities in places and reaffirms the centralities of the urban network in Brazil. Furthermore, we highlight that digital platforms become corporations that extract income from places on a global scale.
Keywords: iFood; digital platforms; centralities